2016
DOI: 10.1016/j.jinf.2016.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of whole blood Xpert® MTB/RIF for diagnosing tuberculosis in children

Abstract: Whole blood Xpert(®) MTB/RIF demonstrated very poor sensitivity, although it may enhance the diagnostic yield in select cases, with culture-negative tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…We identified 66 unique studies that met the inclusion criteria (Ablanedo‐Terrazas 2014; Al‐Ateah 2012; Arockiaraj 2017; Bahr 2015; Bahr 2017; Bera 2015; Bholla 2016; Biadglegne 2014; Blaich 2014; Causse 2011; Che 2017; Christopher 2013; Coetzee 2014; Dhasmana 2014; Dhooria 2016; Diallo 2016; Du 2015; Feasey 2013; Friedrich 2011; Ghariani 2015; Gu 2015; Gursoy 2016; Hanif 2011; Held 2014; Held 2016; Hillemann 2011; Ioannidis 2011; Iram 2015; Jing 2017; Kim 2015a; Li 2017; Ligthelm 2011; Lusiba 2014; Malbruny 2011; Massi 2017; Mazzola 2016; Meldau 2014; Nataraj 2016; Nhu 2014; Ozkutuk 2014; Pandey 2017; Pandie 2014; Patel 2013; Penata 2016; Pink 2016; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Saeed 2017a; Safianowska 2012; Scott 2014; Sharma 2014; Sharma 2016; Solomons 2016; Suzana 2016; Tadesse 2015; Teo 2011; Tortoli 2012; Trajman 2014; Ullah 2017; Vadwa...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 66 unique studies that met the inclusion criteria (Ablanedo‐Terrazas 2014; Al‐Ateah 2012; Arockiaraj 2017; Bahr 2015; Bahr 2017; Bera 2015; Bholla 2016; Biadglegne 2014; Blaich 2014; Causse 2011; Che 2017; Christopher 2013; Coetzee 2014; Dhasmana 2014; Dhooria 2016; Diallo 2016; Du 2015; Feasey 2013; Friedrich 2011; Ghariani 2015; Gu 2015; Gursoy 2016; Hanif 2011; Held 2014; Held 2016; Hillemann 2011; Ioannidis 2011; Iram 2015; Jing 2017; Kim 2015a; Li 2017; Ligthelm 2011; Lusiba 2014; Malbruny 2011; Massi 2017; Mazzola 2016; Meldau 2014; Nataraj 2016; Nhu 2014; Ozkutuk 2014; Pandey 2017; Pandie 2014; Patel 2013; Penata 2016; Pink 2016; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Saeed 2017a; Safianowska 2012; Scott 2014; Sharma 2014; Sharma 2016; Solomons 2016; Suzana 2016; Tadesse 2015; Teo 2011; Tortoli 2012; Trajman 2014; Ullah 2017; Vadwa...…”
Section: Resultsmentioning
confidence: 99%
“…In the index test domain, we thought that all studies had low risk of bias because Xpert test results are automatically generated, the user is provided with printable test results, and the test threshold is prespecified. Regarding applicability, we thought that 42 studies (64%) had low concern because at least 75% of the specimen types in these studies were processed according to WHO recommendations, and 21 studies (32%) had high concern because less than 50% of the specimen types in these studies were processed according to WHO recommendations (Arockiaraj 2017; Causse 2011; Che 2017; Dhasmana 2014; Feasey 2013; Friedrich 2011; Held 2014; Held 2016; Lusiba 2014; Malbruny 2011; Nhu 2014; Pandey 2017; Pohl 2016; Rufai 2015; Rufai 2017a; Rufai 2017b; Suzana 2016; Teo 2011; Tortoli 2012; Ullah 2017; Zeka 2011). Three studies (5%) had unclear concern because the manner of specimen processing was not reported (Bera 2015; Ioannidis 2011), or only 50% of the specimen types were processed according to WHO recommendations (Christopher 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As most cases of TB can be safely and effectively treated after early diagnosis, the high observed mortality rate is associated with poor efficiency in identifying affected individuals and delays in treatment initiation [2]. Traditional methods like smear microscopy and nucleic acid tests like Xpert MTB/RIF (Xpert) rely on sputum as the sample matrix, which leads to poorer test sensitivity in certain populations, like people living with HIV and children, who are more likely to have disease that is extra-pulmonary or paucibacillary in nature and less likely to be able to produce sputum [3,4]. Data show that 20–60% of HIV-positive patients presenting for TB diagnosis are unable to produce a sputum sample [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As for nucleic acid amplification, the Xpert MTB/RIF test has excellent sensitivity for MTB detection even in extrapulmonary specimens; however procedures are required to obtain specimens from the infection sites. Several studies assessing the utility of the Xpert MTB/RIF test using blood samples have reported inadequate sensitivity (Pohl et al, 2016). Therefore, an accurate MTB diagnostic test that uses easily accessible specimens, requiring less invasive procedures, is still needed.…”
Section: Discussionmentioning
confidence: 99%